2019
DOI: 10.1016/j.bbmt.2018.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychological Constructs and Health Outcomes in Hematopoietic Stem Cell Transplantation Patients: A Systematic Review

Abstract: A B S T R A C T Positive psychological constructs (eg, optimism, positive affect) have been independently associated with superior health outcomes across many medical populations. However, there has been little synthesis of the literature examining these associations among patients with hematologic malignancies receiving hematopoietic stem cell transplantation (HSCT). To address this gap we completed a systematic review, using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 79 publications
2
41
1
Order By: Relevance
“…As observed in our cohort, other studies with cancer patients have shown the likelihood for optimism to fluctuate over the course of the cancer care continuum . Numerous studies have highlighted prospective associations between optimism and improved outcomes (including lower depression and anxiety, increased quality of life, and decreased mortality) in the HSCT population . Hence, the potential decrease in report of an important positive emotional trait, such as optimism, justifies the need to explore interventions that could boost optimism and other positive traits in this population.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…As observed in our cohort, other studies with cancer patients have shown the likelihood for optimism to fluctuate over the course of the cancer care continuum . Numerous studies have highlighted prospective associations between optimism and improved outcomes (including lower depression and anxiety, increased quality of life, and decreased mortality) in the HSCT population . Hence, the potential decrease in report of an important positive emotional trait, such as optimism, justifies the need to explore interventions that could boost optimism and other positive traits in this population.…”
Section: Discussionsupporting
confidence: 71%
“…The deliberate engagement in pleasant and meaningful activities also yielded a variety of positive emotional experiences. While family support may be less modifiable for any given patient, interventions that encourage patients to identify and systematically engage in pleasant and meaningful activities could be especially relevant for HSCT patients …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations